2014
DOI: 10.1158/1940-6207.capr-13-0427-t
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Chemopreventive Effect of Polyphenon E in Preventing Early and Metastatic Progression of Prostate Cancer in TRAMP Mice

Abstract: Background Prostate cancer treatment is often accompanied by untoward side effects. Therefore, chemoprevention to reduce the risk and inhibit the progression of prostate cancer may be an effective approach to reducing disease burden. We investigated the safety and efficacy of Polyphenon E, a green tea extract, in reducing the progression of prostate cancer in TRAMP mice. Methods 119 male TRAMP and 119 C57BL/6J mice were treated orally with one of three doses of Polyphenon E (200, 500, 1,000 mg/kg/day) in dri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 65 publications
0
25
0
Order By: Relevance
“…Preclinical studies of GTCs (2023) have shown significant reductions in tumor size and multiplicity in the PCa TRAMP mouse model, as well as potent and selective pro-apoptotic activity in PCa cell lines (16, 1823). Phase I/II studies (2430) have demonstrated good bioavailability and tolerability at doses ranging from 200–1200 mg EGCG per day. Bettuzzi et al reported a significant reduction in prostate cancer in men with HGPIN randomized to receive one-year of EGCG (24, 25).…”
Section: Introductionmentioning
confidence: 99%
“…Preclinical studies of GTCs (2023) have shown significant reductions in tumor size and multiplicity in the PCa TRAMP mouse model, as well as potent and selective pro-apoptotic activity in PCa cell lines (16, 1823). Phase I/II studies (2430) have demonstrated good bioavailability and tolerability at doses ranging from 200–1200 mg EGCG per day. Bettuzzi et al reported a significant reduction in prostate cancer in men with HGPIN randomized to receive one-year of EGCG (24, 25).…”
Section: Introductionmentioning
confidence: 99%
“…One of the studies showed that EPG containing green tea extract significantly reduced circulating tumor cells in breast cancer patients (Samavat et al, 2016). Kim et al (2014) showed that EPG inhibits progression of prostate cancer and metastasis in TRAMP mice (Kim et al, 2014). Another natural compound that affects DNA methylation is curcumin (Liu et al, 2009).…”
Section: Targeting Dna Modifications In Cancer Therapymentioning
confidence: 99%
“…Adverse effects were observed in Swiss Webster mice at 2000 mg/kg/day [276], approximately 200 fold higher than the toxic dose in humans; 1000 mg/kg/day Polyphenon E were well tolerated by C57Bl/6J mice [277]. Similarly, goitrogenic effects were observed in rats only in food concentrations in excess of 0.625%, equivalent to 600 mg/kg/day [278].…”
Section: Risk-benefit Analysismentioning
confidence: 99%